Simultaneous ground-satellite observations of ELF/VLF emissions generated by a strong magnetospheric compression - Claudia Martinez-Calderon; Kazuo Shiokawa; Ondřej Santolík; Satoshi Kurita; Kunihiro Keika; Martin Connors; Ian Schofield; Miroslav Hanzelka; William S. Kurth (Earth, Planets and Space)
Abstract We report, for the first time, simultaneous nightside observations of very low frequency waves associated with a strong sudden impulse and subsequent magnetospheric compression. On 23 December 2014 at 11:15 UT we observed an intense sudden impulse characterized by an increase of SYM-H amplitude (~ 63 nT), solar wind speed (300–420 km/s), and dynamic pressure (2–6 nPa) with northwards interplanetary magnetic field. Two minutes later, the sub-auroral receiver at Athabasca (ATH, 54.7ºN, 246.7ºE, L = 4.3) detected a chorus-like burst centered at ~ 2.2 kHz from 11:17 to 11:20 UT (03 MLT). At the same time, the nearby Van Allen Probes B (RBSP-B) spacecraft, also in the pre-midnight sector, detected an emission with the same temporal and frequency variations suggesting a conjugate event. One minute before this wave burst, RBSP-B also observed hiss below 1.5 kHz, which was not detected at ATH. Magnetospheric compression can lead to betatron acceleration of plasmasheet electrons and enhancement of temperature anisotropy regulating electron cyclotron instability and whistler-mode generation. However, our observations suggest the generation mechanism between hiss and the discrete emissions differed at the beginning of the compression, in addition to them having different propagation to the ground. The decrease of magnetic curvature in the equatorial plane, caused by strong magnetospheric compression, could be responsible for the hiss being observed first. The subsequent stretching of the field lines, increasing the curvature, likely contributed to the generation of the discrete emissions. This discrete emission with mostly oblique wave angles propagated unducted to the ground, while the more field-aligned hiss did not. These results indicate detailed characteristics of the temporal development of hiss/chorus-like wave generation and propagation in response to the global magnetosphere compression associated with a solar wind pressure pulse. Graphical Abstract